The past as a spectacle: The Magnificent Century - (:unkn) unknown (IGI Global, 2014)
Television plays an important role in shaping our perception of the past. Popular television fiction selects, alters, and reinterprets the past in order to appeal to a broad audience. The Magnificent Century (2011- present) is one such television drama, which unfolds during the reign of the Ottoman Sultan, Suleiman the Magnificent. The show, which is the most expensive Turkish television drama to date, promises its audience a spectacle. It has proven a huge success domestically and as of 2013 has been syndicated in 46 other countries. The show's success has been commodified both officially and unofficially. However, this is not to say that it receives unanimous acclaim, even in Turkey. It has provoked controversy due to the representation both of the period and of Suleiman himself. This chapter reflects on the implications of a historical-fiction television series for the contemporary social and political spheres. © 2014 by IGI Global. All rights reserved.